Penerapan Hipnosis Lima Jari Untuk Menurunkan Kecemasan Pada Pasien Dengan Diabetes Melitus - Maulana Abdul Halim; Yuanita Panma (AKPER Pasar Rebo, 2023)
Diabetes melitus is a medical condition in the form of increased blood glucose levels. Changes in body condition that occur in diabetes melitus patients have an influence on the patient's psychology. One of the psychological impacts of Diabetes melitus is anxiety. Nursing intervention that can be done to reduce anxiety is five finger hypnosis. This research method uses a descriptive method with a case study approach accompanied by the application of evidence-based practice. Nursing care was provided to a male patient, aged 65 years, with a medical diagnosis of Diabetes melitus. From the results of the assessment, eight nursing problems were obtained, namely ineffective breathing patterns related to respiratory effort resistance, risk of decreased cardiac output related to changes in preload, changes in afterload, lack of fluid volume related to active fluid loss, vomiting, acute pain related to physiological injurious agents, risk of nutritional deficits related to nausea, insulin insufficiency, activity intolerance related to an imbalance between oxygen supply and demand, self-care deficits related to decreased interest in self-care, weakness, anxiety related to concerns about experiencing a decrease in blood glucose levels. Evidence-based application in cases is carrying out the five finger hypnosis technique for 10-15 minutes with a frequency of 3x/day for three days to reduce the patient's anxiety level. The evaluation results showed that there was a significant decrease in anxiety scores from 30 at the initial assessment to 23 on the third day of implementation. It can be concluded that the five finger hypnosis technique can be applied to diabetes melitus patients to reduce anxiety levels and make patients more relaxed. Nurses can teach the five finger hypnosis technique to patients and families to reduce anxiety